Problems of the Legalization and Dissemination Process - Hari Sanjaya hari (ISNU Sumatera Utara, 2024)
Law number 11 of 2012 concerning the establishment of laws and regulations (Law P3). On the other hand, Law P3 requires all these laws and regulations to be promulgated and placed in the official gazette of the state that has been determined so that they can be considered to come into force. In its application, this problem also spreads to the promulgation process and its enforcement mechanism where there are still many laws and regulations (according to Law P3) that apply without going through the promulgation process. This research aims to 1). How is the process of promulgation in the formation of laws and regulations in Indonesia; 2) How is the dissemination of laws in Indonesia seen from the perspective of the mechanism of its enforcement. This type of research is normative and descriptive, using 4 approaches, namely legislative, historical, comparative and conceptual approaches. The data sources used are primary data and secondary data. Techniques for collecting legal materials through literature studies or document studies. Based on the results of the research, it is concluded that (1) To find out the process of promulgation in the formation of laws and regulations in Indonesia; (2) To find out how the dissemination of laws in Indonesia is seen from the perspective of the mechanism of its enforcement.